P3.61 Trends in adult chlamydia and gonorrhoea prevalence, incidence and urethral discharge case reporting in morocco over 1995–2015 – estimates using the spectrum-sti model. (8th July 2017) - Korenromp, Eline; El-Kettani, Amina; Mahiané, Guy; Bennani, Aziza; Abu-Raddad, Laith; Smolak, Alex; Rowley, Jane; Nagelkerke, Nico; El-Rhilani, Houssine; Alami, Kamal; Hançali, Amina
Abstract : Introduction: Evolving health priorities and resource constraints mean that countries require data on trends in sexually transmitted infections (STI) burden, to inform program planning and resource allocation. Methods: The Spectrum modelling tool estimated prevalence and incidence of gonorrhoea and chlamydia in Morocco's 15–49 year-old population, based on prevalence data adjusted for diagnostic test performance, urban/rural and male/female differences, and missing high-risk populations, and weighted by coverage and representativeness. Results: Gonorrhoea prevalence was estimated at 0.37% (95% confidence interval, 0.14%–1.0%) in women and 0.32% (0.12%–0.87%) in men in 2015; chlamydia prevalences were 3.8% (2.1%–6.4%) and 3.0% (1.7%–5.1%). Corresponding numbers of new cases in 15–49 year-old women and men in 2015 were 79, 598 (23, 918–256, 206) and 112, 013 (28, 700–307, 433) for gonorrhoea, and 291, 908 (161, 064–524, 270) and 314, 032 (186, 076–559, 133) for chlamydia. Gonorrhoea and chlamydia prevalence had declined by 41% and 27%, respectively, over 1995–2015. Prevalence declines probably related to improved STI treatment coverage, and decreasing risk behaviours. Reporting completeness among treated urethral discharge (UD) cases was estimated at 46%–77% in 2015. Clinically reported UD cases corresponded to 13% of all (symptomatic and asymptomatic) gonorrhoea and chlamydia cases. Conclusion: STI declines and improvements in treatment coverage are consistent with Morocco's introduction of syndromic management in 2000, scale-up of prevention interventions, and declining HIV incidence after 2003. While gonorrhoea is four-fold more common as cause of clinical UD cases than chlamydia, Morocco continues to suffer a large, untreated burden of chlamydia. Reliable monitoring of both STIs requires new periodic surveys and/or novel forms of affordable surveillance beyond high-risk populations.